Improvement in efficiency of lignin degradation by Fenton reaction using synergistic catalytic action - Phisit Seesuriyachan (2018)
© 2015 Elsevier B.V. Lignin is a complex aromatic compound and a by-product from the wood pulping process. We used a central composite design to assess the efficiency of synergistic catalysts (Fe 0 , Fe 2+ and Fe 3+ ) and H 2 O 2 in the Fenton process for removal of lignin, aromatic compounds, and chemical oxygen demand (COD) from lignin solution. Results showed that the Fe 0 and H 2 O 2 concentration were the most significant variables in lignin degradation by Fenton reaction, while Fe 2+ and Fe 3+ concentration were the next most important variables. The highest removal efficiencies were obtained with concentration levels of 7.61mg/L Fe 0 , 9.89mg/L Fe 2+ , 14.27mg/L Fe 3+ , and 376.88mg/L H 2 O 2 at pH 3.0 and 35°C. Under these optimal conditions, the efficiencies of removal of lignin, aromatic compounds, and COD were 98.45%, 82.63%, and 100%, respectively, while the removal rates of lignin and aromatic compounds were 23.73mg/L/h and 27.75mg/L/h, respectively. The optimization results revealed that using synergistic catalysts in the Fenton reaction was more effective in treating wastewater and resulted in decreased cost and time.